2016
DOI: 10.1002/jmri.25260
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of MRI parameters within intervertebral discs to the severity of adolescent idiopathic scoliosis

Abstract: We successfully performed an in vivo multiparametric MRI investigation of young patients with adolescent idiopathic scoliosis. The MRI parameters measured within the intervertebral discs were found to be sensitive to intervertebral disc degeneration occurring with scoliosis and to the severity of scoliosis. J. Magn. Reson. Imaging 2016;44:1123-1131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…It was also hypothesized that SWS should increase with deformation severity, but no correlation was observed between SWS and Cobb angle. Huber et al [31] reported that degeneration of IVD is greater within the curvature than in healthy areas, so it is possible that this lack of correlation, in our study, is due to the pooling of different spinal topologies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It was also hypothesized that SWS should increase with deformation severity, but no correlation was observed between SWS and Cobb angle. Huber et al [31] reported that degeneration of IVD is greater within the curvature than in healthy areas, so it is possible that this lack of correlation, in our study, is due to the pooling of different spinal topologies.…”
Section: Discussionmentioning
confidence: 59%
“…Kobielarz et al [35] confirmed this alteration and reported that the number of elastin fiber and collagen I were reduced in AF. In vivo, Huber et al [31] showed by MRI that IVD were more degenerated in scoliosis than healthy IVD whereas Schlösser et al found by CT scan analysis that deformation in 3-D was greater in the IVD than in the vertebral bodies [15].…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis was more severe in untreated children than in MCGR-treated children. Scoliosis itself was proven as a risk factor of IDD [ 27 , 28 , 29 ]. However, in this population, prior MCGR therapy had a more severe effect on disc health than the actual degree of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiparametric magnetic resonance imaging (MRI) has been used to investigate alterations in mechanical properties in the intervertebral disc using linear regressions to relaxation times T 1 , T 2 and T 1rho , magnetization transfer ratios, apparent diffusion coefficients and fractions of anisotropy . Multiparametric MRI, associated with principal component analysis and agglomerative hierarchical clustering, is a promising tool for the classification of degenerated intervertebral discs and for the further identification of biomarkers of the evolution of spine pathologies . However, MRI parameters, including the relaxation time constants T 1 and T 2 , are magnetic field strength dependent.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Multiparametric MRI, associated with principal component analysis and agglomerative hierarchical clustering, is a promising tool for the classification of degenerated intervertebral discs and for the further identification of biomarkers of the evolution of spine pathologies. 32 However, MRI parameters, including the relaxation time constants T 1 and T 2 , are magnetic field strength dependent. In addition, regressions between mechanical properties and MRI parameters are dependent on the tissue degradation state, making in vivo application difficult.…”
mentioning
confidence: 99%